2014
DOI: 10.1124/jpet.113.211714
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Preclinical Characterization of the Histamine H4 Receptor Antagonist JNJ-39758979

Abstract: The histamine H 4 receptor (H 4 R) has been shown to have preclinical involvement in both inflammatory and pruritic responses. JNJ-39758979 [(R)-4-(3-amino-pyrrolidin-1-yl)-6-isopropyl-pyrimidin-2-ylamine] is a potent and selective H 4 R antagonist with a K i at the human receptor of 12.5 6 2.6 nM and greater than 80-fold selectivity over other histamine receptors. The compound also exhibited excellent selectivity versus other targets. JNJ-39758979 showed dose-dependent activity in models of asthma and dermati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
78
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(86 citation statements)
references
References 23 publications
7
78
1
Order By: Relevance
“…This compound has greater than 100-fold selectivity over other histamine receptors as determined by K i (Savall et al, 2014;Thurmond et al, 2014a). In preclinical studies, JNJ 39758979 demonstrated anti-inflammatory activity in animal models of pruritus, asthma, arthritis, and dermatitis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compound has greater than 100-fold selectivity over other histamine receptors as determined by K i (Savall et al, 2014;Thurmond et al, 2014a). In preclinical studies, JNJ 39758979 demonstrated anti-inflammatory activity in animal models of pruritus, asthma, arthritis, and dermatitis.…”
Section: Introductionmentioning
confidence: 99%
“…In an animal model of pruritus in which mice received an intradermal injection of histamine, JNJ 39758979 was efficacious at reducing the bouts of scratching (Savall et al, 2014). In a double-blind, placebo-controlled, randomized, single and multiple ascending dose study to investigate the safety, tolerability, and pharmacokinetics of oral doses of JNJ 39758979 in healthy subjects, no significant safety issues were noted and the compound demonstrated good exposure with a plasma half-life of 124-157 hours after a single oral dose (Thurmond et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…HA H 4 receptor (H 4 R) is of clinical importance because an H 4 R antagonist alleviates HA-induced pruritus in humans (Kollmeier et al, 2014;Seifert, 2014). Several independent research groups have rigorously established the presence of H 4 R in human eosinophils (Raible et al, 1994;O'Reilly et al, 2002;Buckland et al, 2003;Ling et al, 2004;Reher et al, 2012;Thurmond et al, 2014b). H 4 R couples to pertussis toxin (PTX)-sensitive G i proteins to mediate increases in intracellular calcium concentration ([Ca 21 ] i ), shape change, chemotaxis, and inhibition of cAMP-dependent luciferase expression (Oda et al, 2000;Hofstra et al, 2003;Buckland et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…It needs to be evaluated whether the efficacy of H 4 receptor antagonists in other ethnic groups, women, and children and in various diseases is different. It should also be noted that JNJ 39758979 will not become a clinically approved drug because, in independent clinical trials, the compound, unfortunately, was found to induce agranulocytosis (Thurmond et al, 2014a), a life-threatening toxic effect. It is assumed that agranulocytosis is intrinsic to the chemical structure of the compound and is not attributed to an effect mediated via the H 4 receptor (Kollmeier et al, 2014;Thurmond et al, 2014a).…”
mentioning
confidence: 99%
“…Recently, Thurmond et al (2014a) have characterized the pharmacokinetic and pharmacodynamic properties of the potent and selective H 4 receptor antagonist JNJ 39758979 in healthy humans. JNJ 39758979 has a very long plasma half-life (124-157 hours) and reduces histamine-induced shape change in eosinophils ex vivo.…”
mentioning
confidence: 99%